2019
DOI: 10.1136/rapm-2018-000015
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the innervation of posterior knee joint capsule: implication for image-guided intervention

Abstract: Background and objectivesPeripheral nerve block is an important component of the multimodal analgesia for total knee arthroplasty. Novel interventional techniques of ultrasound-guided nerve block supplying the posterior knee joint capsule require knowledge of the innervation of the posterior capsule. The objectives of this cadaveric study were to determine the course, frequency, and distribution of the articular branches innervating the posterior knee joint capsule and their relationships to anatomical landmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 22 publications
5
102
0
3
Order By: Relevance
“…In a recent anatomical study, articular branches of the TN were found to be the main source of innervation to the entire posterior knee joint capsule 10. Superiorly, the posterior capsule also received additional innervation from the GBPON and PBCFN.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent anatomical study, articular branches of the TN were found to be the main source of innervation to the entire posterior knee joint capsule 10. Superiorly, the posterior capsule also received additional innervation from the GBPON and PBCFN.…”
Section: Discussionmentioning
confidence: 96%
“…So, it is apparent that the previous studies using radiofrequency of 3 genicular nerves might have failed to block the lion's share of nerves supplying the joint . There are a few recent studies in which the nerves supplying the knee were described very well with their anatomical locations . Recently, Lam described the technique to block 7 genicular nerves supplying the knee joint .…”
Section: Discussionmentioning
confidence: 99%
“…Real‐time visualization of the periarticular arteries on the medial side of the knee (ie, saphenous branch of the descending genicular artery and anastomotic branches between the superior and inferior medial genicular arteries) is paramount to promptly avoid unintentional bleeding . Simply, a transverse view at the level of the medial femoral condyle can be used to promptly identify the vascular structures of this anatomic region: ie, descending genicular and superior medial genicular arteries running behind the vastus medialis obliquus muscle (online Supplemental Figure 3, A and C) …”
Section: Description Of the Techniquementioning
confidence: 99%
“…15 Simply, a transverse view at the level of the medial femoral condyle can be used to promptly identify the vascular structures of this anatomic region: ie, descending genicular and superior medial genicular arteries running behind the vastus medialis obliquus muscle (online Supplemental Figure 3, A and C). 16…”
Section: Complications and Side Effectsmentioning
confidence: 99%